2020
DOI: 10.1093/mnras/staa624
|View full text |Cite
|
Sign up to set email alerts
|

Energy optimization in extrasolar planetary systems: the transition from peas-in-a-pod to runaway growth

Abstract: Motivated by the trends found in the observed sample of extrasolar planets, this paper determines tidal equilibrium states for forming planetary systemssubject to conservation of angular momentum, constant total mass, and fixed orbital spacing. In the low-mass limit, valid for superearth-class planets with masses of order m p ∼ 10M ⊕ , previous work showed that energy optimization leads to nearly equal mass planets, with circular orbits confined to a plane. The present treatment generalizes previous results by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…Common sizing of multiplanet systems has previously been found for Kepler systems (e.g., Millholland et al 2017;Wang 2017;Weiss et al 2018;Gilbert & Fabrycky 2020). From a planet formation standpoint, Adams et al (2020) found that energy optimization occurs when planets are nearly equal in mass for low-mass (super-Earth/sub-Neptune) planet systems, which is consistent with what we see with K2-138. Though, we note that the outer planets of K2-138 have larger radii than the inner planets, a trend consistent with the findings of Ciardi et al (2013), Millholland et al (2017, Kipping (2018), and Weiss et al (2018), possibly the result of enhanced photoevaporation closer to the star.…”
Section: G CMsupporting
confidence: 90%
“…Common sizing of multiplanet systems has previously been found for Kepler systems (e.g., Millholland et al 2017;Wang 2017;Weiss et al 2018;Gilbert & Fabrycky 2020). From a planet formation standpoint, Adams et al (2020) found that energy optimization occurs when planets are nearly equal in mass for low-mass (super-Earth/sub-Neptune) planet systems, which is consistent with what we see with K2-138. Though, we note that the outer planets of K2-138 have larger radii than the inner planets, a trend consistent with the findings of Ciardi et al (2013), Millholland et al (2017, Kipping (2018), and Weiss et al (2018), possibly the result of enhanced photoevaporation closer to the star.…”
Section: G CMsupporting
confidence: 90%
“…The longest contact phases, naturally found for our least massive systems (with a total system mass of 20 M ), lasts for about 10 Myr, and occur in systems with initial mass ratios near one. The majority of our contact binary models have the tendency to evolve towards equal component masses, corresponding to the lowest energy state of binary systems (Adams et al 2020). We find that the longer a system spends time in contact, the higher the likelihood that it attains a mass ratio of unity before merging on the main sequence.…”
Section: Discussionmentioning
confidence: 82%
“…The discovery that more than half of all Sun‐like stars host close‐in planets intermediate in size between the Earth and Neptune (“sub‐Neptune size planets”) is perhaps the most profound discovery from NASA's Kepler mission—see Figure 1 (Fressin et al., 2013; Howard et al., 2012). The existence of these planets in large numbers wasn't predicted by planet formation theories (Ida & Lin, 2004; Mordasini et al., 2009), and their provenance remains hotly debated (e.g., F. C. Adams et al., 2020; Chiang & Laughlin, 2013; Ginzburg et al., 2016; Hansen & Murray, 2013; Izidoro et al., 2017; Lee & Chiang, 2016; Lee et al., 2014; Raymond & Cossou, 2014; Raymond et al., 2008; Raymond, Boulet, et al., 2018; L. A. Rogers et al., 2011; Schlichting, 2014).…”
Section: Introductionmentioning
confidence: 99%